1978
DOI: 10.1159/000181193
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Medium pH on <i>p</i><i>-</i>Aminohippurate Transport in Rat Kidney Fragments

Abstract: Addition of many oxidizable substrates to medium often enhances p-aminohippurate (PAH) transport by incubating renal tissue. Since the oxidation of various substrates by rat kidney tissue may change medium pH and this pH change has not been considered by many in conclusions, we followed the effects of medium pH on the magnitude and kinetics of in vitro PAH transport. Two previous studies employing rat kidney slices reported different optimal medium pH for PAH accumulation, i.e. pH 6.5 and pH 8.0. By repeating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1979
1979
1982
1982

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…We observed that when renal tissue is incubated for 90 min in phosphate-buffered medium con taining acetate, pH increases gradually to >7.8. We had previously found that PAH accumulation is significantly augmented at medium pH > 7.8 compared to medium pH 7.4 [2], Since the degree of enhancement to PAH accumulation in renal fragments in duced by 10 mM acetate (20-30%) is of the same magnitude as that produced by alkalo sis (medium pH > 7.8) alone (+20%), we hy pothesized that the in vitro effect of acetate on PAH uptake might be mediated in large part through the induced alkalosis [2], The present studies strengthen this hypo thesis. As previously reported [6], maximum tissue PAH uptake was reached by 30 min, and was maintained through 90 min when no substrate was present ( fig.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…We observed that when renal tissue is incubated for 90 min in phosphate-buffered medium con taining acetate, pH increases gradually to >7.8. We had previously found that PAH accumulation is significantly augmented at medium pH > 7.8 compared to medium pH 7.4 [2], Since the degree of enhancement to PAH accumulation in renal fragments in duced by 10 mM acetate (20-30%) is of the same magnitude as that produced by alkalo sis (medium pH > 7.8) alone (+20%), we hy pothesized that the in vitro effect of acetate on PAH uptake might be mediated in large part through the induced alkalosis [2], The present studies strengthen this hypo thesis. As previously reported [6], maximum tissue PAH uptake was reached by 30 min, and was maintained through 90 min when no substrate was present ( fig.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, two observations were made on kidney tissue incubating in vitro that may help answer this question, at least in rats. First, the pH of phosphate-buffered medium consistently rises from 7.4 to greater than 7.8 when renal cortical tissue is incubated in 10 mM acetate [2], Second, PAH accumulation is signifi cantly higher in 'alkalotic medium' (pH>7.8) than at pH 7.4 [3. 4], It was pos tulated [2] that acetate-stimulated PAH ac cumulation was secondary to the rise in medium pH rather than a direct effect from substrate metabolism.…”
mentioning
confidence: 99%
See 1 more Smart Citation